2020
DOI: 10.1161/circheartfailure.119.006863
|View full text |Cite
|
Sign up to set email alerts
|

Lower Rates of Heart Failure and All-Cause Hospitalizations During Pulmonary Artery Pressure-Guided Therapy for Ambulatory Heart Failure

Abstract: Background: Ambulatory hemodynamic monitoring with an implantable pulmonary artery (PA) sensor is approved for patients with New York Heart Association Class III heart failure (HF) and a prior HF hospitalization (HFH) within 12 months. The objective of this study was to assess the efficacy and safety of PA pressure-guided therapy in routine clinical practice with special focus on subgroups defined by sex, race, and ejection fraction. Methods: This multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 21 publications
8
100
0
7
Order By: Relevance
“…Subset analysis of the CHAMPION trial has shown that the sensor can also lead to better haemodynamic management of patients with preserved ejection fraction and lower rates of hospitalization when compared with standard therapy. 20 A recently published post-approval study of 1200 patients in multiple practice settings demonstrated a 58% reduction in HF hospitalizations and a 28% reduction in all-cause hospitalizations during the year after implantation of CardioMEMS. 21 …”
Section: Haemodynamic Monitoring Using Cardiomemsmentioning
confidence: 99%
“…Subset analysis of the CHAMPION trial has shown that the sensor can also lead to better haemodynamic management of patients with preserved ejection fraction and lower rates of hospitalization when compared with standard therapy. 20 A recently published post-approval study of 1200 patients in multiple practice settings demonstrated a 58% reduction in HF hospitalizations and a 28% reduction in all-cause hospitalizations during the year after implantation of CardioMEMS. 21 …”
Section: Haemodynamic Monitoring Using Cardiomemsmentioning
confidence: 99%
“…Recently, studies investigating invasive remote monitoring strategies have shown a beneficial effect in more symptomatic patients [ 81 , 82 , 83 , 84 ]. However, these invasive strategies are limited due to their higher costs and its invasive nature.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…16 PA-pressure monitoring also reduces HF hospitalisations in routine clinical practice. [17][18][19] In one study, the mean rate of daily pressure transmission was 76%, suggesting that patient adherence to monitoring may be one component of its success. 19…”
Section: Remote Assessment Of Haemodynamicsmentioning
confidence: 99%